Budaya Modifikasi Gigi dalam Konteks Antropologi Forensik di Indonesia - Alaydrus, Sayf Muhammad (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 2 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i02.p02, 2022)
In a forensic anthropology context, the human identification process requires two equally important aspects—biological and sociocultural. Unfortunately, the latter is often overlooked. Albeit, culture can leave important markers on the human body. Thus, it may aid forensic anthropologists to identify the demographic and cultural characteristics of an unknown individual. This review article’s purpose is to discuss varieties of cultural dental modification in Indonesia and its significance in forensic identification. This paper reviewed at least 15 primary works of literature acquired from Google Scholar, while a handful of other literature is additional. Then, the data from said literature was extracted into four subchapters. Consumption of betel nut can influence various dental characteristics, such as dental staining and calculus. This paper also discusses dental sharpening and inlay. Dental ablation is a relatively ancient culture that symbolizes mourn or marriage and is often misidentified as other types of AMTL. Daily activities, e.g., diet and tooth brushing habits also influence human dentition. Based on the literature review, the author concluded that various types of dental modification are performed by many cultures across Indonesia, with one culture bearing unique features that differentiate them from other cultures. During the identification process, it is important to know what type of modification is performed, whose dentitions are modified, and which teeth are modified—since it may bare significance to the individualization process.